Ensuring the right to a safe environment under martial law - ALYONKIN, Олексій (Ius Modernum, 2024)
Separate legal mechanisms for ensuring the right to a safe environment under martial law are highlighted. An analysis of the environmental protection legislation of Ukraine formed in recent years was carried out in order to establish guarantees for the realization, conservation, protection and restoration of environmental rights of a person in the conditions of large-scale armed aggression. The purpose of the article is a theoretical and applied understanding of the concept meaning of "ensuring the right to a safe environment under martial law", the state of its normative and legal consolidation in Ukraine, and the formulation of proposals for improving the relevant legal regulation. Methods used: dialectical, hermeneutic, systemic, analysis and synthesis, induction and deduction, formal-legal and others. It has been established that ensuring the right to an environment safe for life and health is a rather complex and multifaceted process, the final result of which depends on many factors, among which the destructive impact on the natural environment of the consequences of military operations stands out. In connection with this, a number of normative legal acts have been implemented in Ukraine, the main purpose of which is to simplify the procedures for carrying out restoration work to eliminate the consequences of war and ensure the right to a safe environment. The importance of the considered legal acts, from the point of view of ensuring environmental rights, consists in recording the negative effects of military actions on the state of the environment and compensation for the damage caused to it, on access to environmental information and its distribution, on general and special nature use, etc. It was emphasized that the key point in overcoming the negative consequences of the impact on the environment in the conditions of martial law should be, among other things, normatively established measures of economic activity in the field of water resources use. It is noted that the problems in the environment, which must be overcome by the adoption of relevant draft laws, remain unresolved due to the complexity of the procedures that were provided by Ukrainian legislation for peacetime conditions. It is emphasized that the norms of the current legislation of Ukraine must take into account the factors of the consequences of conducting military operations, including their impact on the surrounding natural environment, and therefore, on ensuring the right to a safe environment under martial law.